Early modern toleration: new approaches - Kaplan, Benjamin J.; Geraerts, Jaap (Early modern themes, 2024)
Introduction : early modern toleration -- "To preserve and instill the beloved peace" -- religious invective and confessional coexistence under the peace of Augsburg / Allyson F. Creasman -- The acoustics of peace : singing and religious coexistence in seventeenth-century Mechelen / Matthew Laube -- Tuning Catholicism in the Dutch Republic. Catholic soundscapes in a Calvinist Society, c. 1600-1750 / Carolina Lenarduzzi -- At the crossroads of identity : conversos and moriscos in inquisitorial Spain (sixteenth -- seventeenth centuries) / Natalia Muchnik -- Memory, toleration, and conflict after the French wars of religion / David van der Linden -- Constitutional dynamism and demographic diversity in early modern confessional coexistence : Dutch reformed refugees in the Holy Roman Empire, 1554-1596 / Jesse Spohnholz -- Ambivalent neighbours : sensory and spatial dynamics of religious exchange in early modern Tuscany / Nicholas Terpstra -- Crossing borders? Conversions and mixed marriages in Ottoman Bilād al-Shām (seventeenth-eighteenth centuries) / Felicita Tramontana -- Interacting and engaging : historiographical introduction Catholic merchants in British commerce in the age of mercantilism / Giada Pizzoni -- Conquest, colonialism and religious conflict in the Moluccas in the early seventeenth century / Hendrik E. Niemeijer -- A middle path to toleration? Sharing sacred spaces in Bautzen and Wetzlar, 1523-1625 / David M. Luebke -- From contested space to sacred topography : Jews, protestants and Catholics in reformation Cracow / Anat Vaturi -- Confessional boundaries and transconfessional spaces in late seventeenth- and eighteenth- century British North America / Susanne Lachenicht.